Pancreatic Cancer: What About Screening and Detection? - Konstantinou, Froso; Syrigos, Kostas N; Saif, Muhammad Wasif (JOP. Journal of the Pancreas, 2013)
Pancreatic cancer is the fourth leading cause of cancer-related death in both sexes in the United States. In 2013, it is expected to account for 7% of all female cancer deaths and 6% of all male cancer deaths in the USA. Late presentation of the disease and poor prognosis even after complete operative resection, justify the necessity for early detection of pancreatic cancer as well as identifying high-risk individuals (screening). Herein, the authors summarize the data presented at the 2013 American Society of Clinical Oncology (ASCO) Annual Meeting regarding screening and early detection of pancreatic cancer (Abstracts #4045 and #4052). Image: Salvation (Sotiria) mosaic. Antakya, Turkey.